2022
DOI: 10.3390/cancers14133083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Beckwith–Wiedemann Syndrome Spectrum with Associated Tumors and Consequences for Clinical Practice

Abstract: Beckwith–Wiedemann syndrome (BWS, OMIM 130650) is a congenital imprinting condition with a heterogenous clinical presentation of overgrowth and an increased childhood cancer risk (mainly nephroblastoma, hepatoblastoma or neuroblastoma). Due to the varying clinical presentation encompassing classical, clinical BWS without a molecular diagnosis and BWS-related phenotypes with an 11p15.5 molecular anomaly, the syndromic entity was extended to the Beckwith–Wiedemann spectrum (BWSp). The tumor risk of up to 30% dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…BWSp is a disorder predisposing to tumors of embryonic origin that arise during childhood, usually up to 10 years of age [ 4 , 5 , 27 ]. Data on tumor risk and histotype prevalence in adult BWSp patients are very limited because the clinical phenotype mitigates with age and a follow-up of large series of adults with BWSp has not been performed [ 1 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BWSp is a disorder predisposing to tumors of embryonic origin that arise during childhood, usually up to 10 years of age [ 4 , 5 , 27 ]. Data on tumor risk and histotype prevalence in adult BWSp patients are very limited because the clinical phenotype mitigates with age and a follow-up of large series of adults with BWSp has not been performed [ 1 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest risk (2.6%) is associated with IC2 LoM, and the related histotypes are hepatoblastoma (0.7%), rhabdomyosarcoma (0.5%) and neuroblastoma (0.5%). Furthermore, in the subset of BWSp patients with MLID, to date, no specific tumor-risk estimates have been defined [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…BWS is a well-defined tumor predisposition syndrome, and 7.4–10% of patients develop embryonal tumors (WT, hepatoblastoma, neoblastoma, adrenal cell carcinoma) in childhood, usually before the age of 7 years [ 13 , 14 , 25 , 26 , 27 , 28 , 29 ]. Mussa et al [ 25 ] studied the characteristics of 318 BWS patients and reported a significant correlation between malignant neoplasms and lateralized overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Certain syndromes, backed by robust clinical evidence, stand out for their well documented association with specific tumor predisposition. Beckwith–Wiedemann syndrome (BWS) is intricately linked to the heightened likelihood of developing Wilms tumor, hepatoblastoma, and adrenal cortical carcinoma, setting this syndrome apart from the others above as exhibiting a higher risk profile [32]. PTEN hamartoma tumor syndrome (thyroid, endometrial, and breast cancer) has guidelines [29–31,33].…”
Section: Comorbiditiesmentioning
confidence: 99%